VALIDITY OF PHYSICS MODULE INTEGRATING CREATIVE THINKING ABILITY IN MOMENTUM AND IMPULSE MATERIALS - Yogi Aulia; Hufri Hufri (Universitas Negeri Padang, 2022)
This exploration depends on the low understudy learning results, the low understudy learning results, among others, brought about by the low innovative reasoning skill of understudies. This is partly due to the fact that in learning students are not accustomed to developing their creative thinking skills, this condition is due to the lack of teaching materials that facilitate students in improving their creative thinking skills which results in their learning outcomes. The solution is to develop a Physics learning module that integrates students' creative thinking skills. The purpose of this study was to determine the validity, practicality and effectiveness of the Physics learning module on Momentum and Impulse material for class X SMA. The type of research used is research and development (R&D) and the object of the research is a physics module that integrates creative thinking skills. The design model used is the ADDIE model. The research steps include: analysis, design, development, implementation and evaluation. Based on the data investigation that has been finished, the normal worth of the module validation is 89% which is in the very valid criteria, it very well may be reasoned that the physics module of integration of creative thinking skills on momentum and impulse material can be said to be valid and can be utilized in class X material science learning in high school